SENI DAN PERDAMAIAN: Analisis Kritis tentang Seni sebagai Medium Transformasi Konflik - Fauzie Wiriadisastra; Rudi Setiawan (Kongregasi Hati Kudus Yesus (RSCJ) Indonesia, 2026)
This study aims to analyze the role of art as a medium for conflict transformation and peacebuilding through the perspective of Johan Galtung’s conflict transformation theory. This inquiry is important because art not only has the potential to serve as a means of reconciliation and peacebuilding but can also function as a medium for disseminating hatred and legitimizing symbolic violence. The study employs a qualitative approach using a library research method. The data derive from various scholarly sources that discuss conflict transformation theory, philosophy of art, aesthetics, the psychology of empathy, and peace studies. The study analyzes the data through a descriptive-critical approach by examining the concepts of creativity, nonviolence, and empathy, which constitute the core components of Galtung’s conflict transformation theory. The findings demonstrate that creativity plays a crucial role in developing alternative and peaceful solutions to conflict, while nonviolence constitutes an intrinsic characteristic of art that distinguishes it from practices of direct violence. At the same time, empathy does not always generate peace because, under certain conditions, it can encourage group exclusivism and hostility toward others. Consequently, conflict transformation requires the development of intergroup empathy (outgroup empathy) that transcends the boundaries of social identity. The study also finds that, according to several transcendental aesthetic theories, media intended to disseminate hatred do not fully satisfy the fundamental characteristics of art. These findings suggest that art possesses normative potential as a medium of peacebuilding when it strengthens creativity, nonviolence, and inclusive forms of empathy. The originality of this study lies in its effort to integrate Johan Galtung’s conflict transformation theory with the philosophy of art and aesthetic studies in order to explain the conceptual boundary between art as a medium of peace and art as a medium of hatred.